Facile electrodeposition fabrication of raspberry-like gold microspheres decorated polydiphenylamine nanohybrid coated electrode for efficient direct methanol fuel cell application. (15th December 2022) - Sankar Sivasankarapillai, Vishnu; Veni Keertheeswari, N.; Chahal, Priyanka; Mohammad Wabaidur, Saikh; Ponnusamy, Vinoth Kumar; Dhanusuraman, Ragupathy
Graphical abstract: Highlights: Simple two-step electro-fabrication of gold and polydiphenylamine over FTO electrode. Raspberry–like microspheres of Au decorated over PDPA conducting polymer network. Synergistic effect of gold microspheres and PDPA nanonetwork shows efficient MOR. Rct value of FTO/PDPA/AuMS is lower than FTO/PDPA shows low charge resistance. Excellent stability of FTO/PDPA/AuMS electrode compared with FTO/PDPA. Abstract: In this work, a simple two-step electrodeposition strategy has been successfully developed to fabricate morphology-controlled gold microspheres (AuMS) decorated polydiphenylamine (PDPA) nanohybrid modified FTO electrode. The physicochemical characterization of PDPA/AuMS modified electrode has been explored using XRD and SEM/EDX mapping techniques. Results showed the controlled synthesis of uniform-sized raspberry-like AuMS were decorated in the PDPA matrix to form the electrocatalytically active PDPA/AuMS nanohybrid material on the FTO electrode. As-fabricated PDPA/AuMS modified FTO electrode was used as an efficient electrocatalyst for methanol oxidation reaction under an alkaline environment for fuel cell applications. Cyclic voltammetry, chronoamperometry, and electrochemical impedance spectroscopy techniques were employed to investigate the as-prepared electrode's electrochemical responses and methanol oxidation reaction (MOR). PDPA/AuMS hybrid electrode showed 1.04 mA/cm 2 as the current density at a lower scan rate (50 mV/ sec ) with a lower potential value of 0.43 V, which indicates the excellent electrocatalytic activity of the fabricated electrode. Moreover, the as-prepared electrode showed more extended stability and durability (60 min) towards MOR due to the combined existence of AuMS and PDPA matrix, which enhances the catalytic property. Based on the above results, an as-prepared PDPA/AuMS nanohybrid composite can be applied as a potential electrocatalyst/alternative electrode for direct methanol fuel cell (DMFC) applications.